Three-dimensional axial dispersion dynamics of granular flow in the rolling-regime rotating drum - Yang, Shiliang (2020)
The dispersion characteristics of the granular material frequently encountered in many chemical industries play an important role in the system operation since it is related to the solid residence time, and thus further influence the heat and mass transfer behavior of the whole process. To shed some light, the discrete element method (DEM) is employed here to study a three-dimensional rotating drum, with the key focus being the axial dispersion characteristics of the solid phase. Our results prove the natural existence of a preferential channel for axial dispersion spanning the entire drum length, which provides insights on the region where the most extensive axial segregation effects are expected. Furthermore, we show that the axial solid dispersion coefficients adhere to normal frequency distributions in the active region, passive region and the entire drum. Also, increasing the rotating speed enhances while increasing the fill level diminishes the axial dispersion intensity in the system. Collectively, the results here provide new and valuable insights on the axial dispersion characteristics in the rotating drum, which is useful for the further understanding and optimization of the system.